2007
DOI: 10.1128/iai.01841-06
|View full text |Cite
|
Sign up to set email alerts
|

Interaction ofCandida albicanswith Adherent Human Peripheral Blood Mononuclear Cells IncreasesC. albicansBiofilm Formation and Results in Differential Expression of Pro- and Anti-Inflammatory Cytokines

Abstract: Monocytes and macrophages are the cell types most commonly associated with the innate immune response against Candida albicans infection. Interactions between the host immune system and Candida organisms have been investigated for planktonic Candida cells, but no studies have addressed these interactions in a biofilm environment. In this study, for the first time, we evaluated the ability of C. albicans to form biofilms in the presence or absence of adherent peripheral blood mononuclear cells (PBMCs; enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 51 publications
8
115
1
2
Order By: Relevance
“…1A and B). Analysis of adherent PBMC, which include multiple cellular subsets (30), showed that Ad35 and Ad26 similarly colocalized with late endosomes by 2 h postinfection (data not shown). Both Ad35 and Ad26 accumulated in the late endosomal compartment to significantly higher levels than Ad5 at 2 h postinfection as measured by both LAMP1 (3.1-and 6.4-fold greater colocalization, respectively; P ϭ 0.0088 and P ϭ 0.0001, respectively) and M6P (5.8-and 9.8-fold greater colocalization, respectively; P Ͻ 0.0001 for both) colocalization.…”
Section: Resultsmentioning
confidence: 99%
“…1A and B). Analysis of adherent PBMC, which include multiple cellular subsets (30), showed that Ad35 and Ad26 similarly colocalized with late endosomes by 2 h postinfection (data not shown). Both Ad35 and Ad26 accumulated in the late endosomal compartment to significantly higher levels than Ad5 at 2 h postinfection as measured by both LAMP1 (3.1-and 6.4-fold greater colocalization, respectively; P ϭ 0.0088 and P ϭ 0.0001, respectively) and M6P (5.8-and 9.8-fold greater colocalization, respectively; P Ͻ 0.0001 for both) colocalization.…”
Section: Resultsmentioning
confidence: 99%
“…C. albicans biofilms exhibit increased resistance to drugs and antifungal host defenses (14,23,29,30). Compared with free-floating C. albicans, biofilms have been shown to preferentially induce production of cytokines involved in driving Th1 or Th17 responses (14,48). In the case of DS, it is possible that a C. albicans biofilm formed on the denture continually inoculates the host mucosa, leading to tissue-associated biofilm formation.…”
Section: Enture Stomatitis (Ds) Is An Inflammatory Fungal Infectionmentioning
confidence: 99%
“…albicans readily forms biofilms on denture material in vitro and in vivo, which consist of a network of hyphae and yeast encased in a polysaccharide matrix (34,(39)(40)(41). C. albicans biofilms exhibit increased resistance to drugs and antifungal host defenses (14,23,29,30). Compared with free-floating C. albicans, biofilms have been shown to preferentially induce production of cytokines involved in driving Th1 or Th17 responses (14,48).…”
Section: Enture Stomatitis (Ds) Is An Inflammatory Fungal Infectionmentioning
confidence: 99%
“…Similarly, Chandra et al (2007) showed that peripheral blood mononuclear cells (PBMCs) enhanced the ability of the yeast, Candida albicans, to form biofilms and that the majority of PBMCs were localized to the basal and middle layers of the biofilm. They also found that only viable PBMCs enhanced Candida biofilm formation and that PBMCs cell surface components did not contribute to this biofilm enhancement; the biofilm-enhancing effect is mediated by a soluble factor released into the medium, and that the supernatant collected from co-cultures contained differential levels of pro-and anti-inflammatory cytokines.…”
Section: Biofilm:immune Cell Interactionsmentioning
confidence: 99%